2012
DOI: 10.2147/oajsm.s33284
|View full text |Cite
|
Sign up to set email alerts
|

 Running speed during training and percent body fat predict race time in recreational male marathoners

Abstract: BackgroundRecent studies have shown that personal best marathon time is a strong predictor of race time in male ultramarathoners. We aimed to determine variables predictive of marathon race time in recreational male marathoners by using the same characteristics of anthropometry and training as used for ultramarathoners.MethodsAnthropometric and training characteristics of 126 recreational male marathoners were bivariately and multivariately related to marathon race times.ResultsAfter multivariate regression, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 40 publications
1
43
0
Order By: Relevance
“…Also, for recreational marathoners, men showed the same predictor variables for the race time including body fat ( β =0.504) and running speed during training sessions ( β =-0.57) [41] . For recreational female marathoners, however, the circumference of calf ( r =-0.41, P =0.02) and running speed during training sessions ( r =-0.60, P =0.0005) were positively associated with marathon race times in the multi-variate analysis [29] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, for recreational marathoners, men showed the same predictor variables for the race time including body fat ( β =0.504) and running speed during training sessions ( β =-0.57) [41] . For recreational female marathoners, however, the circumference of calf ( r =-0.41, P =0.02) and running speed during training sessions ( r =-0.60, P =0.0005) were positively associated with marathon race times in the multi-variate analysis [29] .…”
Section: Discussionmentioning
confidence: 99%
“…In recreational male marathoners, race time correlated to body fat percentage and running speed during training sessions [41] . Marathon race time was faster when body fat was lower and running speed during training was higher.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies recognized mean training speed or pace as the best predictor of marathon performance time. It should be noted that other training indices, such as mean distance per workout, maximum distance run per week, number of workouts per week, and number or previous marathons run, were not found to be predictive of marathon performance time 7,8…”
Section: Discussionmentioning
confidence: 99%
“…The increasing number of recreational runners participating in major running events, including the marathons held in New York, Chicago, London, and Berlin, suggested a need to develop analyses that relate race performance to variables easily detected or self-monitored, like training characteristics. Several studies in the last 30 years have shown that a combination of physiological, anthropometric, and training characteristics can predict performance in long-distance running 28…”
Section: Introductionmentioning
confidence: 99%
“…During practice training for a marathon, the athletes received highly intensive training recipes to improve their aerobic and anaerobic thresholds during their preparation and for a specific period of time. Their extremely low fat percentage, commonly found in long-distance runners or endurance athletes, could be an important factor for the prediction of their marathon race time [28] and correlates to their performance [2]. However, excessive sports activity can be deleterious to the young female population, because of their lower BMI and menstrual irregularity [7].…”
Section: Discussionmentioning
confidence: 99%